Sea warfare - Kipling, Rudyard 1865-1936 (Uniform Press Ltd., 2015)
A collection of Rudyard Kipling's articles describing the role of the Navy during the First World War. Published to coincide with the 150th anniversary of Rudyard Kipling's birth